Processing birth experiences: A content analysis of women's preferences. (February 2019) - Sigurðardóttir, Valgerður Lísa; Gamble, Jennifer; Guðmundsdóttir, Berglind; Sveinsdóttir, Herdís; Gottfreðsdóttir, Helga
Abstract: Background: Negative birth experiences may have adverse effects on the wellbeing of women and babies. Knowledge about useful interventions to assist women in processing and resolving negative birth experiences is limited. Objective: To explore women's experience and preferences of reviewing their birth experience at a special midwifery clinic. Design: The study is a qualitative content analysis of women's written text responses to semi-structured questions, included in a retrospective study. Setting: A special counselling clinic, 'Ljáðu mér eyra', at Landspitali University Hospital in Reykjavik, provides women with an opportunity to review their birth experience and discuss their fears about an upcoming birth with a midwife. Sample, recruitment and data collection: A questionnaire was sent to all women attending the clinic from 2006–2011 ( n  = 301). Of the 131 women completing and returning the questionnaire, 125 provided written responses to the open-ended questions. The questionnaire consisted of demographic and reproductive characteristics of women, questions about why they attended the clinic, whether their expectations were fulfilled, helpful components of the interview and open-ended questions about women's views of the process. Data analysis: Data on participant characteristics, the reason for attending the clinic, whether the interview fulfilled their expectations and helpful components were analysed using quantitative descriptive data, while written responses to semi-structured questions were analysed using content analysis. Findings: The main reasons for attending the clinic were a previous negative birth experience, anxiety about the upcoming birth, and/or loss of control during a prior birth. Two themes and three subthemes were identified. The overarching theme was ' on my terms ' with the subthemes of 'being recognised', 'listening is paramount' and 'mapping the unknown'. The final theme was 'moving on'. Key conclusions: Women want to be recognised and invited to review their birth experience in a tailored conversation on their terms. By fulfilling their expectations of reviewing the birth experience, they regained control and strength to move on. Implications for practice: Findings support the importance of recognising women's need to review their birth experiences and offer an intervention to reflect on their perceptions. A discussion of the birth experience should be a routine part of maternity services.